Climate Change Resilience and Control in Villages: Efforts to Achieve Sustainable Development Goals - Aulia, Nurul; Mustari, Nuryanti; Burhanuddin, Burhanuddin; Mappasere, Fatmawati A. (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The absence of natural disaster control due to climate change can have an impact on economic and environmental aspects. The purpose of this study is to evaluate the role of village governments in implementing the Climate Change Response Village Programme with the SDGs Concept in Gowa Regency. This research uses qualitative and quantitative research methods, whose data are obtained from observations, interviews, document studies and questionnaires of 100 samples from the total population determined using purposive sampling techniques. The theory used in this research is Stuflebeam's CIPP evaluation. The results showed that the village programme in Barombong sub-district was generally successful in achieving its objectives. Although there are some obstacles such as the lack of facilities and infrastructure, finance, and the need to improve human resources. The level of effectiveness of the implementation of the village programme in Barombong Sub-district resulted that the three indicators studied in 5 locations were in the good category. So it is necessary to improve aspects of communication and coordination with the local government of Gowa Regency to be more optimistic about the implementation of the Disaster and Climate Change Response Village programme in achieving the Disaster Ratio Index target of 0 for all households.